Continuous Positive Airway Pressure Improves Renal Function in Obese Patients With Obstructive Sleep Apnea Syndrome - Perticone, Maria; Maio, Raffaele; Scarpino, Paola Elisa; Mancuso, Luana; Volpentesta, Mara; Caroleo, Benedetto; Suraci, Edoardo; Sciacqua, Angela; Sesti, Giorgio; Perticone, Francesco (Frontiers in Medicine, 2021)
Background: Obstructive sleep apnea syndrome (OSAS) is an independent risk factor for cardiovascular morbidity and mortality, and it has a detrimental effect on renal function. Obesity is the major risk factor for OSAS, and represents a risk factor for chronic kidney disease. Continuous positive airway pressure (CPAP) is the suggested therapy for moderate-to-severe OSAS. We designed this study to evaluate the effect of CPAP on estimated glomerular filtration rate (e-GFR) in a cohort of obese patients with moderate-to-severe OSAS and normal renal function. Methods: We enrolled 198 obese subjects, divided into two groups (OSAS+ and OSAS-), on the basis of cardiorespiratory monitoring; mild OSAS patients (n= 33) were excluded from the study, thus the analyses were conducted on 165 patients. Comparisons between groups were made by Student t test or χ2 test as appropriate. Linear regression analyses were used to assess the relationship between baseline e-GFR and different covariates and, in the OSAS+ group, between Δe-GFR and different covariates. A multivariate regression analysis was performed to determinate the independent predictor of the Δe-GFR. Results: OSAS+ subjects showed significantly increased values of systolic blood pressure, HOMA, pulse wave velocity, high-sensitivity C reactive protein and uric acid compared with OSAS- group. OSAS+ group showed significantly lower values of e-GFR and increased values of microalbuminuria. At linear regression analysis e-GFR resulted significantly and inversely related to AHI in the whole study population and in the two groups. After six months of CPAP therapy, OSAS+ subjects showed an improvement in respiratory parameters, as well as a significant increase in e-GFR values (104.2+19.0vs 84.0+13.1 ml/min/1.73 m2, P<0.0001). At multiple regression analysis, Δ apnea/hypopnea index (AHIa) resulted the main independent predictor of Δe-GFR explaining 22% of its variation. Conclusions: Obese OSAS patients show significantly lower values of e-GFR, even if in the normal range, compared with obese non-OSAS subjects. After six months of CPAP, e-GFR significantly improved (+20 ml/min/1.73m2) and ΔAHIa resulted the most important independent predictor of Δe-GFR.